Current status and research progress of endoscopic retrograde cholangiopancreatography in the diagnosis and treatment of biliary and pancreatic system diseases - Yuehu, Li; Jianp, Gong; Dong, Shu (International Surgery Journal, 2021)
Endoscopic retrograde cholangiopancreatography (ERCP) has been used clinically since the 1960s, after nearly half a century of development, it has become an important method for clinical diagnosis and treatment of biliary and pancreatic system diseases. In recent years, with the continuous updating of endoscopy equipment, the advancement of endoscopists’ technology, and the progress in understanding of biliary and pancreatic diseases, the application of ERCP in the diagnosis and treatment of biliary and pancreatic diseases has become more extensive, and the diagnosis and treatment procedures have become more standardized. At the same time, the diagnostic role of ERCP has declined slightly with the advancement of noninvasive imaging technology. But, its intervention role in treatment is more prominent, reducing dependence on traditional trauma therapy. The aim of the study was to summarize the application status of ERCP technology in biliary and pancreatic system diseases and the research progress in recent years.